Factors Affecting Effective Service Delivery by Micro Finance Institutions towards Poverty Reduction - Ahmed, Garba Ahmed (2011)
Today widespread poverty is one of the major problems facing our economics and its alleviation one of her major agendas under the UN millennium development goals. In recent years microfinance has emerged as an important instrument to relieve in the developing countries. Today there are more than 7000 micro lending institutions providing loans to more than 25 million poor individuals across the world. However these institutions face some serious challenges, especially in less developed countries where the proportion of people in poverty is high. The existing microfinance in Nigeria serves less than 1 million people out of 40 million being the potential number that need the service. Also, the aggregate micro credit facilities in Nigeria, account for about 0.2 percent of the GDP and is less than one percent of total credit in the economy. Addressing this situation inadequately would further accentuate the problem and slow growth and development of the country thus it is of importance to an economy to tackle such issues. We find that the microfinance institutions charge interest rate as high as up to 100% for lending and pay as low as 5% on savings. Furthermore the length on the loan repayment period set is not efficient for effective use of microcredit. The paper aims to archive how those factors are of importance for effective service delivery by micro finance institutions. The findings show the importance of moving towards effective micro finance institutions in achieving the said objective of reducing poverty. Recommendation and options are suggested for future research to increase the body of knowledge on microfinance.